2021
DOI: 10.3389/fphy.2021.649852
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Confirmation Bias and Peer Pressure in Opinion Dynamics

Abstract: Confirmation bias and peer pressure are regarded as the main psychology origins of personal opinion adjustment. Each show substantial impacts on the formation of collective decisions. Nevertheless, few attempts have been made to study how the interplay between these two mechanisms affects public opinion evolution on large-scale social networks. In this paper, we propose an agent-based model of opinion dynamics which incorporates the conjugate effect of confirmation bias (characterized by the population identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Some of them introduced various new factors [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], such as the opinion leader [ 23 ], the memory [ 24 ], the expression and private opinion [ 25 ], the fuzzy inference [ 26 ], the stubbornness [ 27 , 28 , 29 ], and the noise [ 23 , 30 , 31 , 32 , 33 ], to the classic bounded confidence model. Others consider different possibilities of evolutionary mechanisms of the system [ 27 , 34 , 35 , 36 , 37 , 38 , 39 ], such as the heterogeneous bounded confidence [ 27 , 34 , 35 ], the heterogeneous pressure [ 36 , 37 ], and the circular opinion space [ 38 , 39 ]. One of the most important topics in the bounded confidence model is how to promote the opinion consensus.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them introduced various new factors [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], such as the opinion leader [ 23 ], the memory [ 24 ], the expression and private opinion [ 25 ], the fuzzy inference [ 26 ], the stubbornness [ 27 , 28 , 29 ], and the noise [ 23 , 30 , 31 , 32 , 33 ], to the classic bounded confidence model. Others consider different possibilities of evolutionary mechanisms of the system [ 27 , 34 , 35 , 36 , 37 , 38 , 39 ], such as the heterogeneous bounded confidence [ 27 , 34 , 35 ], the heterogeneous pressure [ 36 , 37 ], and the circular opinion space [ 38 , 39 ]. One of the most important topics in the bounded confidence model is how to promote the opinion consensus.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its importance there have been efforts to integrate this bias in opinion dynamics models [17,18,19]. More specifically, in [20] the authors proposed a model where agents ignore opinions that are too different from their own.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the main factors that shape people's opinions are confirmation bias and social influence [84]. According to Vicario et al [125], the observed polarization of offline and online communities might be the result of the conjugate effect of these two forces.…”
Section: Introductionmentioning
confidence: 99%